The Influence of Intellectual Capital, Good Corporate Governance (GCG) and Company Size on the Financial Performance of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) in 2020-2023. - M. Rafli Wiranata; Geby Citra Ananda (Yayasan Multidimensi Kreatif, 2024)
This study aims to determine the effect of Intellectual Capital, Good Corporate Governance (GCG) and Company Size on the Financial Performance of Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (Bei) in 2020-2023. This type of research is quantitative. The number of samples in this study were 16 companies, the data analysis techniques used in this study were classical assumption tests (normality, multicollinearity and heteroscedasticity), multiple linear analysis tests and hypothesis testing (t test, F test and coefficient of determination).